Diagnosis and Treatment of a Patient With Severe Combined Immunodeficiency Due to a Novel Homozygous Mutation in the IL-7Rα Chain - Mansour, Rana; Bsat, Yasmin El; Fadel, Anthony; El-Orfali, Youmna; Noun, Dolly; Tarek, Nidale; Kabbara, Nabil; Abboud, Miguel; Massaad, Michel J. (Frontiers in Immunology, 2022)
The interleukin-7 receptor (IL-7R) is expressed on lymphoid cells and plays an important role in the development, homeostasis, survival, and proliferation of T cells. Bi-allelic mutations in the IL-7Ra chain abolish T cell development and function resulting in severe combined immunodeficiency disease. In this manuscript, we investigate a 1 year-old patient born to consanguineous parents, who suffered from autoimmune hemolytic anemia since birth associated with recurrent severe infections. Flow cytometric analysis of the patient’s peripheral blood demonstrated elevated numbers of B and NK cells, decreased numbers of T cells, defective thymic output, a predominance of memory T cells, and absent T cell proliferation. Next Generation Sequencing identified a novel homozygous pathogenic mutation in IL7RA (c.379G>A) that resulted in aberrant IL7RA RNA splicing and absent IL-7Ra expression. The patient was successfully transplanted using her HLA-matched relative as donor. One year after transplant, the patient is clinically stable with normal reconstitution of donor T cells that express IL-7Ra, a significant increase in the percentages of recent thymic emigrant and peripheral T cells, normalization of naïve and memory T cells, and restoration of her T cell’s proliferative response. Therefore, using genetic and functional approaches, we identified a novel deleterious mutation in IL-7Ra that results in T-B+NK+ phenotype, and report successful hematopoietic stem cell transplantation of the patient. This represents the first bedside-to-bench-and-back case entirely performed on a patient with severe combined immunodeficiency at the American University of Beirut Medical Center.